2021
DOI: 10.3389/fvets.2021.730390
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 on Pet Food Bank Servicing: Quantifying Numbers of Clients Serviced in the Vancouver Downtown Eastside, British Columbia, Canada

Abstract: Previous research has focused on the benefits and difficulties of pet ownership in people, who are experiencing homelessness. However, many pet services, such as pet food banks, serve a more varied population of people. Furthermore, the effect of the COVID-19 pandemic has not been documented within the context of pet food banks. Vancouver's Downtown Eastside (DTES) population comprises a notable proportion of the city's overall population and has a high density of people who are experiencing financial hardship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…COVID-19, on the one hand, separated society through social isolation and distancing; on the other hand, it united communities through caring, affection, sympathy, and solidarity [ 47 ]. COVID-19-triggered economic challenges not only impacted individual capacity to access veterinary services but also cut community-based service agency budgets, particularly not-for-profit organizations, which provide vulnerable animals and people with material and financial support [ 80 ]. As COVID-19 shaped their lives, women's gendered caretaking roles moved beyond family and friend circles into the broader community.…”
Section: Resultsmentioning
confidence: 99%
“…COVID-19, on the one hand, separated society through social isolation and distancing; on the other hand, it united communities through caring, affection, sympathy, and solidarity [ 47 ]. COVID-19-triggered economic challenges not only impacted individual capacity to access veterinary services but also cut community-based service agency budgets, particularly not-for-profit organizations, which provide vulnerable animals and people with material and financial support [ 80 ]. As COVID-19 shaped their lives, women's gendered caretaking roles moved beyond family and friend circles into the broader community.…”
Section: Resultsmentioning
confidence: 99%
“…Many organizations also embraced a “community-supported sheltering” model during the COVID-19 pandemic and created new programs or increased the availability of existing programs that proactively address the most common reasons for shelter intake (e.g., housing insecurity, access to veterinary care, and access to pet food and supplies). Examples of these programs include pet food and supply banks ( 20 ), advocating for pet-friendly rental policies ( 21 ), shifting animal control operations from a punishment to support model ( 22 ), offering co-sheltering options for individuals in crisis (e.g., individuals experiencing homelessness or domestic violence) ( 23 ), One Health vaccine clinics ( 24 ), and examining how social and economic inequities affect shelter intake ( 25 , 26 ). There are a number of other emerging program areas that may also be contributing to the measured decreases in total intake throughout the study period, including low- or no-cost spay–neuter services and other preventive veterinary care ( 27 , 28 ); door-to-door outreach in underserved communities to overcome barriers in access to veterinary care ( 29 ), trap-neuter-return ( 30 32 ), and return-to-field programs ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, I have selected the services sector to learn about the effect of COVID-19. Erden and Aslan ( 17 ) concluded that banks are included in the services sector that has been impacted by the pandemic ( 18 ). The term “bank” appears for the first time in history in Italy.…”
Section: Introductionmentioning
confidence: 99%